Influence of the urban structure on the patterns of daily mobility of a feminized work in the Metropolitan Area of Mexico City (2018)
One of the consequences of segregated urban structure is the increase in the distances of displacement between the center and the periphery. Its effects have not been homogeneous throughout the territory. For the analysis of the distribution of the commuting patterns of a highly feminized occupation such as paid domestic work, we opted for the exploratory analysis of spatial data, applying the Moran Index and the Local Autocorrelation Index. Space (LISA). The results obtained show a greater external mobility of women, with long distances both in distance and time, from municipalities in the eastern zone of the Metropolitan Area of Mexico City, which are characterized by having high levels of poverty.